Comparison of Prognosis Between Microscopically Positive and Negative Surgical Margins for Primary Gastrointestinal Stromal Tumors: A Systematic Review and Meta-Analysis - Liu, Zhen; Zhang, Yichunzi; Yin, Han; Geng, Xiuzhu; Li, Sishang; Zhao, Jinrong; Zeng, Ziyang; Ye, Xin; Yu, Jianchun; Feng, Fan; Kang, Weiming (Frontiers in Oncology, 2022)
Background The prognostic impact of microscopically positive margin (R1) on primary gastrointestinal tumor remains unclear. The current meta-analysis aimed to clarify this question. Methods Literature search was performed through Pubmed, Embase, Web of Science and Cochrane Library up to Nov 23, 2020. The pooled disease-free (DFS) and overall survival (OS) between R1 and negative margin (R0) were estimated with random-effects model. Results Twenty studies with 6465 patients were included. Compared with R0 resection, R1 was associated with poor DFS of patients did not receive adjuvant Imatinib (HR: 1.62, 95% CI: 1.26-2.09; P=0.48, I2=0%; reference: R0). This negative impact of R1 disappeared in the era of adjuvant Imatinib (HR: 1.23, 95% CI: 0.95-1.60; P=0.38, I2=6%; reference: R0). Subgroup analysis was performed according to tumor site (stomach, rectum and mixed sites) and use of adjuvant Imatinib (no and yes). For gastric GIST, R1 margin had no significant influence on DFS regardless of the use of adjuvant Imatinib (without Imatinib: HR: 1.35, 95% CI: 0.22-8.36; P=0.16, I2=50%; reference: R0; with Imatinib: HR: 2.24, 95% CI: 0.32-15.60; P=0.84, I2=0%; reference: R0). Notably, rectal GIST with R1 margin who even received adjuvant Imatinib still had poor DFS compared with R0 resection (HR: 3.79, 95% CI: 1.27-11.31; P=0.54, I2=0%; reference: R0). R1 margin had no influence on OS of GIST. Conclusion R1 margin does not lead to poor prognosis of GIST in stomach regardless of the use of adjuvant Imatinib. And extra attention beyond standard adjuvant Imatinib is warranted for rectal GIST once R1 margin occurs.